PERAN STAKEHOLDERS DALAM PENURUNAN ANGKA PREVALENSI STUNTING DI KOTA SEMARANG - Nur Alifisyiam, Ferita; Rina Herawati, Augustin; Purnaweni, Hartuti (Journal of Public Policy and Management Review, 2024)
The success of Semarang City in reducing the stunting prevalence rate by 10.4% in 2022 cannot be separated from the involvement of stakeholders who played a role. This achievement was better than the national target (14%) and was the lowest stunting prevalence rate in Central Java. The aim of this research is to identify stakeholders who are involved and analyze their role in reducing the prevalence of stunting in Semarang City. The method used in this research is descriptive qualitative with data collection techniques through interviews, observation and literature study. This research uses Maryono et.al's theory to identify stakeholder and Bryson's theory for analyzing roles stakeholders which are involved. The results of this research show that stakeholders Those involved in successfully reducing stunting prevalence rates in Semarang City were identified into three categories, namely (1) primary stakeholder (target communities, posyandu and puskesmas); (2) secondary stakeholder consisting of private parties; and (3) key stakeholder (Bappeda, Dinas Kesehatan, Dinas Pengendalian Penduduk dan Keluarga Berencana, and Dinas Ketahanan Pangan Kota Semarang). Meanwhile, the role of stakeholders is divided into four types, namely key players, context setters, subjects, and crowd. The recommendations given in this research are (1) the Semarang City Government needs to apply the concept of community empowerment in handling stunting in order to increase community independence; and (2) the cross-sector program innovations owned by the Semarang City Government can be applied to other regional governments as a pilot project in reducing stunting prevalence rates.